Allgemeine projektive Normalisationen für Geradenkongruenzen - Lumiste, Ü. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Лумисте. Общие проективные оснащения конгруэнций прямыхJ. Lumiste. Bendros tiesių kongruencijų projektyvinės normalizacijos